(3JMaI GdCNjGQ aj aVGFd GdCfUGQs - (3fhQ GdOjf Hf MSjf GdCfUGQjs
(3ChdgG (B:s
(3GdMeO ddg QGaY efGQ GdeLGgOjf (B[ (3GdegGLQjf ?(B] (3hGdCfUGQ s
(3BNQgG (B:s
(3hcGf GdaQGZ ef JYdjbgG ai Ghd TgQ TYHGf GdeYXe ef TghQ SfI (B988(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B96 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs